2017
DOI: 10.1093/pm/pnx037
|View full text |Cite
|
Sign up to set email alerts
|

Does Cervical Interlaminar Epidural Steroid Injection with Low-Dose Lidocaine Cause Objective Upper Extremity Weakness? A Preliminary Study

Abstract: The present data suggest that CIESI with an injectate volume of 3 mL that includes 1 mL of 1% lidocaine may result in objective upper extremity weakness that is above the minimum threshold of perception in a subset of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…We previously published a single-arm cohort study demonstrating that 20% of participants experience a ≥20% decrease in strength in at least one myotome as measured by dynamometry after CIESI with 1.0 mL of 1% lidocaine used as the diluent. 15 In the present study, a higher dose of lidocaine was intentionally used: 2.0 mL of 1% lidocaine for a total injectate volume of 4 mL. Despite this higher dose of lidocaine, and surprisingly counter to our hypothesis, 41.7% and 50.0% of participants in the CIESI-L and CIESI-S groups, respectively, experienced a ≥20% decrease in strength in at least one myotome between 20 and 30 min postinjection, resulting in no between-group difference (RR 0.83 (95% CI, 0.56 to 1.23)).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously published a single-arm cohort study demonstrating that 20% of participants experience a ≥20% decrease in strength in at least one myotome as measured by dynamometry after CIESI with 1.0 mL of 1% lidocaine used as the diluent. 15 In the present study, a higher dose of lidocaine was intentionally used: 2.0 mL of 1% lidocaine for a total injectate volume of 4 mL. Despite this higher dose of lidocaine, and surprisingly counter to our hypothesis, 41.7% and 50.0% of participants in the CIESI-L and CIESI-S groups, respectively, experienced a ≥20% decrease in strength in at least one myotome between 20 and 30 min postinjection, resulting in no between-group difference (RR 0.83 (95% CI, 0.56 to 1.23)).…”
Section: Discussionmentioning
confidence: 99%
“…14 We reported similar findings in a single-arm cohort study, wherein 20% of participants experienced a clinically meaningful decrease in upper extremity strength, as assessed by dynamometry, in at least one myotome after a single CIESI injection with 1.0 mL of 1% lidocaine used as a diluent. 15 Given a lack of clear evidence or a consensus recommendation for the use of local anesthetic as a diluent during CIESI, the present study was designed to determine if low-dose lidocaine used during CIESI results in (1) clinically significant upper extremity weakness and (2) immediate pain relief when compared with saline. We hypothesized that CIESI with lidocaine would cause an objective transient decrease in upper extremity strength and a significant immediate decrease in pain compared with saline.…”
Section: Introductionmentioning
confidence: 99%
“…For example, because sedation compromises mental status, cognition, and reaction time, it is necessary for clinicians to strongly advise against driving after ESI procedures in which such agents are administered. Likewise, driving should be avoided following ESI in which local anesthetic is included in the injectate (regardless of sedation use during the procedure), as temporary sensorimotor impairment may occur in a subset of patients [6,7] and delayed-onset sensorimotor block and loss of consciousness may occur following unintentional subdural local anesthetic injection [8][9][10]. Further, one small prospective case-control study of lumbar selective nerve root block demonstrated delayed driving reaction time equating to an increase in stopping distance of 3.8 meters if traveling 100 km/hr both immediately and at two week follow-up [11].…”
Section: Introductionmentioning
confidence: 99%